Penerapan fasilitas belajar menggunakan aplikasi podcast dalam meningkatkan minat belajar - Nila Sudarti; Novia Juita; Havid Ardi (Universitas Asahan, 2023)
The world of education is currently experiencing new innovations in an effort to increase student interest in learning in the industrial revolution 4.0 era which continues to spur educators to continue to innovate. This study aims to find out how the process of increasing student learning in utilizing podcast media in the world of education, educators are constantly required to race in developing learning tools, especially in the era of the industrial revolution 4.0. Research conducted using descriptive analysis method. The form of the instrument in this study used several media such as smartphones, Google podcasts, journals, notebooks, and several other writing instruments. Data collection techniques carried out in this study used literature study. The literature study was carried out by researchers by collecting several journal references related to podcast media and how they are applied and their benefits in learning in the era of the industrial revolution 4.0. Based on the research results, it is known that there are several educators who have used podcast media, including the accounts of Addie Huzaini, Aryo Damar and Irwansyah. In the learning process the use of podcast media is also found in several other research journals.